Instanton vibrations of the 3-Skyrmion - HOUGHTON, CONOR JAMES (American Physical Society, 1999)
The Atiyah-Drinfeld-Hitchin-Manin matrix corresponding to a tetrahedrally symmetric 3-instanton is calculated. Some small variations of the matrix correspond to vibrations of the instanton-generated 3-Skyrmion. These vibrations are decomposed under tetrahedral symmetry and this decomposition is compared to previous knowledge of the 3-Skyrmion vibration spectrum.
PUBLISHED
Keywords: Pure & Applied Mathematics